The black hole X-ray binary MAXI J1348–630 in quiescence. Issue 1 (9th September 2022) - Carotenuto, F; Corbel, S; Tzioumis, A
ABSTRACT: The properties of the disc/jet coupling in quiescent black hole low mass X-ray binaries (BH LMXBs) are still largely unknown. In this paper, we present the first quasi-simultaneous radio and X-ray detection in quiescence of the BH LMXB MAXI J1348–630, which is known to display a hybrid disc/jet connection that depends on the accretion rate. We performed deep X-ray and radio observations using the Chandra X-ray Observatory and the Australia Telescope Compact Array. MAXI J1348–630 is detected for the first time in quiescence at an X-ray luminosity L X = (7.5 ± 2.9) × 10 30 ( D /2.2 kpc) 2 erg s −1 : one of the lowest X-ray luminosities observed for a quiescent BH LMXB, possibly implying a short orbital period for the system. MAXI J1348–630 is also detected in radio at L R = (4.3 ± 0.9) × 10 26 ( D /2.2 kpc) 2 erg s −1 . These detections allow us to constrain the location of MAXI J1348–630 on the radio/X-ray diagram in quiescence, finding that the source belongs to the standard ( radio-loud ) track in this phase. This provides a strong confirmation that hybrid-correlation sources follow the standard track at low luminosities and down to quiescence, thus improving our knowledge of the disc/jet connection in BH LMXBs.